American Medical Society for Sports Medicine Recommended Sports Ultrasound Curriculum for Sports Medicine Fellowships. Issue 1 (January 2015) - Finnoff, Jonathan T.; Berkoff, David; Brennan, Fred; DiFiori, John; Hall, Mederic M.; Harmon, Kimberly; Lavallee, Mark; Martin, Sean; Smith, Jay; Stovak, Mark
Abstract : Abstract: The following sports ultrasound (SPORTS US) curriculum is a revision of the curriculum developed by the American Medical Society for Sports Medicine (AMSSM) in 2010. Several changes have been made to the curriculum with the primary aim of providing a pathway by which a sports medicine fellow can obtain sufficient SPORTS US training to become proficient in the core competencies of SPORTS US. The core competencies of SPORTS US are outlined in the learning objectives section of this document. The term "SPORTS US" was purposefully chosen rather than "musculoskeletal ultrasound" (MSK US) because it was recognized by the panel that the evolving field of SPORTS US encompasses non-MSK applications of ultrasound such as the FAST examination (focused assessment with sonography for trauma). Although the SPORTS US core competencies in this curriculum are all MSK in nature, they represent the minimum SPORTS US knowledge a sports medicine fellow should acquire during fellowship. However, additional training in more advanced MSK and non-MSK applications of ultrasound can be provided at the fellowship director's discretion. Completion of this SPORTS US curriculum fulfills the American Institute of Ultrasound in Medicine's (AIUM) requirements to perform an MSK US examination and the prerequisites for the American Registry for Diagnostic Medical Sonography's (ARDMS) MSK sonography certification examination. Abstract : Supplemental Digital Content is Available in the Text.